BREAKING DOWN EDUCATIONAL BOUNDARIES: A STUDY OF SPECIAL SCHOOLS' PEDAGOGICAL METHODS - Nzuzi, Claire Mbemba (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
In the last two decades, efforts within the social sector have sought to enhance the inclusion and engagement of vulnerable children as a means to counteract exclusion. Integration and participation stand as vital components for upholding human dignity and ensuring the realization of human rights. This movement resonates particularly within the European community, housing over 30 million individuals grappling with physical, sensory, and mental impairments. Correspondingly, the World Health Organization approximates that nearly seven million inhabitants of France are affected by disabilities, while Africa harbors an estimated eighty million. In Congo, the disabled population was tallied at 300,000 in 1996, evolving significantly to encompass roughly one-third (1/3) of the populace today, approximately one million (1,000,000). Guided by this trajectory, legislative actions and directives, especially those pertaining to school integration classes, have underscored the significance of educating disabled children at the primary level. Anchored in the 2030 Agenda for Sustainable Development, a global initiative underpinned by 17 Sustainable Development Goals (SDGs), this commitment towards comprehensive progress enjoys the participation of all member nations. Within this context, Goal 4, focused on achieving quality education, carries particular relevance to the disabled community, with specific emphasis on target 4.5 to ensure equitable access to education for vulnerable groups including those with disabilities. The Republic of Congo, deeply entrenched in these universal concerns, acknowledges the inherent right of every Congolese child to education, as per School Law No. 25/95. Enacted on November 17, 1995, this legislation outlines the necessity for specialized schools catering to the unique needs of handicapped individuals. Central to this is the "network of special schools," exemplified by the "school of ten houses" in Brazzaville, the focal point of our research. This study delves into the pedagogical approach of these special schools, aiming to elucidate their role in nurturing inclusivity and empowering individuals with disabilities.